MULTITEMPORAL LANDSAT DATA TO QUICK MAPPING OF PADDY FIELD BASED ON STATISTICAL PARAMETERS OF VEGETATION INDEX (CASE STUDY: TANGGAMUS, LAMPUNG) - I Made Parsa; Dede Dirgahayu (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2013)
Paddy  field  has  unique  characteristics  that  distinguish  it  from  other  plants.  Before it planting, paddy field is always flooded so that the appearance is dominated by water (aqueous phase). Within the  growth  of rice, field  conditions  will  be  increasingly  dominated  by  greenish rice  plants.While at the end, the rice plants will turn yellow indicating for harvesting. During flooding stage, the normalized difference vegetation index (NDVI) of pady field is negative. The negative value of NDVI of paddy field will ultimately increase to the maximum value at the maximum vegetative growth. TheNDVI of paddy field will decrease from generative phase until harvest and after harvest. The objective of  this  study  was  to  perform  the vegetation  index  analyses for multitemporal  Landsat  imagery of paddy field. The results showed that the difference of vegetation index values (maximum - minimum)of  paddy  field  were greater than the  difference  of vegetation index  values of  other land  uses.  Such differences values can be used as indicator to map land for rice. The evaluation results with reference data showed that the mapping accuracy (overall accuracy) was of 87.4 percent.